Table of Content - -, (Arab Journal for Sciences and Research Publishing, 2025)
Table of Content:1. The Role of Modern Information Technologies in Promoting Scientific Research in Saudi Universities: Challenges, Requirements, and Future OpportunitiesMs. Ashwaq Abdulhakeem Alsabaan2. The Impact of Virtual Reality Technologies in Digital Media on Audience Experience: An Applied Study on Real Estate Events in The Kingdom of Saudi Arabia During the Year 2025Dr. Sara Saad Al-Dawsari,Dr. Sadiq Ali Mubarak Al-Shuwaikhat3. The Implications of Polygamy on the Demographic Reality in Palestinian Society and the Stance of Israeli Civil Laws Towards ItDr. Samy Garad Abu Freach4. The Philosophy of Divinity: From Platonism to Orthodoxy – A Study in the Thought of Theodoret of CyrrhusDr. Rony Emil Saiid5. Translation is a cultural and human civilizational manifestation, and technical skills for the rapprochement of peoples and nationsDr. Jehad Faiz Al-Islam6. MATLAB Implementation of Effects of Fifth Generation on Free SpaceEng. Rayan Abdelazeem Haboub, Prof. Khalid Hamid Bilal
Keywords: Arab Journal of Sciences & Research Publishing